5 Metal-Catalyzed C—H Activation - Xing,Y.-K.; Fang,P.; Wang,Z.-H.; Mei,T.-S. (Electrochemistry in Organic Synthesis, 2022)
Synthetic organic electrochemistry is currently experiencing a renaissance, the merger of electrochemistry with transition-metal-catalyzed C—H activation would provide not only an environmentally friendly approach, but also offer new opportunities that conventional transition-metal catalysis may not have achieved. In this chapter, we summarize the recent progress made in catalytic C—H activation reactions using organometallic electrochemistry, including C—C, C—O, C—N, C—halogen, and C—P bond-forming reactions.
Keywords: Referencework; organic electrochemistry; electrosynthesis; C—H activation; organometallic electrochemistry; transition-metal catalysis; arene functionalization; cyclization